Bone marrow mesenchymal stem cell-derived extracellular vesicles alleviate diabetes-exacerbated atherosclerosis via AMPK/mTOR pathway-mediated autophagy-related macrophage polarization - Libo Liu; Ziyu An; Huan Zhang; Xueqi Wan; Xin Zhao; Xueyao Yang; Jinfan Tian; Xiantao Song (Cardiovascular Diabetology)
Abstract Introduction Bone marrow-derived mesenchymal stem cell-derived extracellular vesicles (BMSC-EVs) are widely used for therapeutic purposes in preclinical studies. However, their utility in treating diabetes-associated atherosclerosis remains largely unexplored. Here, we aimed to characterize BMSC-EV-mediated regulation of autophagy and macrophage polarization. Methods EVs were isolated from the supernatant of cultured BMSCs and characterized with transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and western blotting. A diabetes-related atherosclerotic ApoE−/− mouse model was established through feeding with a high-fat diet (HFD) and streptozotocin (STZ). Histopathological analyses were carried out using Oil Red O, H&E, and Masson staining of the aorta. TEM and immunohistochemistry (IHC) were applied to evaluate autophagy, and immunofluorescence (IF) was used to identify macrophage polarization. RAW264.7 macrophages were induced with oxidized low-density lipoprotein (ox-LDL) and high glucose (HG), co-cultured with BMSC-EVs, and analyzed for macrophage proliferation, migration, and foam cell formation. RAW264.7 cells were transduced with autophagy marker mRFP-GFP-LC3 lentivirus and analyzed with IF and western blotting. Results Diabetic mice (DA group) had larger aortic plaque areas and lower collagen content than the HFD mice. BMSC-EV treatment significantly reduced blood glucose, LDL levels, and aortic plaque areas while increasing collagen content. BMSC-EV-treated aortas contained a higher number of autophagosomes/autolysosomes, with increased expression of LC3BII correlating with decreased P62 levels and a lower proportion of M1 macrophages. In vitro, BMSC-EVs inhibited proliferation, migration, and foam cell formation in ox-LDL and HG-induced activated RAW264.7 cells. These effects were reversed by the autophagy blocker bafilomycin A1. Consistent with the in vivo findings, BMSC-EVs elevated levels of the autophagy-related protein LC3BII/I and decreased P62 in ox-LDL and HG-induced RAW264.7 cells. These cells also expressed the M1 macrophage markers CD86 and iNOS, but showed reduced expression of the M2 marker Arg-1. Further, BMSC-EVs decreased AMPKα and mTOR phosphorylation levels, which were blocked by the AMPK inhibitor compound C. Conclusions BMSC-EVs attenuate diabetes-exacerbated atherosclerosis by inhibiting vascular macrophage proliferation, migration, and foam cell formation via AMPK/mTOR signaling-regulated autophagy and macrophage polarization. BMSC-EVs thus hold promise as therapeutic agents for atherosclerosis. Graphical Abstract Extracellular vesicles derived from bone marrow mesenchymal stem cells may mitigate diabetes-aggravated atherosclerosis by regulating AMPK/mTOR-mediated autophagy-related macrophage polarization and inhibiting macrophage proliferation, migration, foam cell formation, and cholesterol transport.